2021
DOI: 10.3390/ijms22158127
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Associated Cancer Biomarkers: A Requirement for Early Diagnosis

Abstract: Globally, HIV/AIDS and cancer are increasingly public health problems and continue to exist as comorbidities. The sub-Saharan African region has the largest number of HIV infections. Malignancies previously associated with HIV/AIDS, also known as the AIDS-defining cancers (ADCs) have been documented to decrease, while the non-AIDS defining cancer (NADCs) are on the rise. On the other hand, cancer is a highly heterogeneous disease and precision oncology as the most effective cancer therapy is gaining attraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 144 publications
(173 reference statements)
0
9
0
Order By: Relevance
“…There are critical stages and molecules that play a role in their oncogenicity [ 8 ] including blocking tumour suppressor molecules such as P53 or by activation of oncogenes [ 9 ]. For example, human immunodeficiency virus (HIV) has potential cancer-causing effects [ 10 , 11 ]. This virus leverages multiple mechanisms that eventually result in three cancer types namely, Kaposi sarcoma (KS), non-Hodgkin lymphoma (NHL), and invasive cervical cancer (ICC) by different mechanisms [ 10 , 11 ].…”
Section: Oncogenic Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are critical stages and molecules that play a role in their oncogenicity [ 8 ] including blocking tumour suppressor molecules such as P53 or by activation of oncogenes [ 9 ]. For example, human immunodeficiency virus (HIV) has potential cancer-causing effects [ 10 , 11 ]. This virus leverages multiple mechanisms that eventually result in three cancer types namely, Kaposi sarcoma (KS), non-Hodgkin lymphoma (NHL), and invasive cervical cancer (ICC) by different mechanisms [ 10 , 11 ].…”
Section: Oncogenic Virusesmentioning
confidence: 99%
“…For example, human immunodeficiency virus (HIV) has potential cancer-causing effects [ 10 , 11 ]. This virus leverages multiple mechanisms that eventually result in three cancer types namely, Kaposi sarcoma (KS), non-Hodgkin lymphoma (NHL), and invasive cervical cancer (ICC) by different mechanisms [ 10 , 11 ].…”
Section: Oncogenic Virusesmentioning
confidence: 99%
“…Previous investigation demonstrated that the core of personalized medicine for cancer lies in the discovery and development of biomarkers, which reveal information that leads to the diagnosis, prognosis, and therapy of the disease ( Dlamini et al, 2021 ). Besides, a previous research pointed out that uncertainty of prognosis is the main reason that patients with hematologic malignancies receive aggressive therapy near end of life ( Iizuka-Honma et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… 2 Among HIV patients, the prevalence of lung cancer has also been increasing. 3 , 4 According to the Global Cancer Statistics report, lung cancer has the third highest mortality rate among all malignancies. 5 And the survival rate of HIV‐infected lung cancer patients is lower than that of regular lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the use of highly active antiretroviral therapy (HARRT), the survival time of HIV patients has been increasing 2 . Among HIV patients, the prevalence of lung cancer has also been increasing 3,4 . According to the Global Cancer Statistics report, lung cancer has the third highest mortality rate among all malignancies 5 .…”
Section: Introductionmentioning
confidence: 99%